Shank postsynaptic scaffolding proteins in autism spectrum disorder: Mouse models and their dysfunctions in behaviors, synapses, and molecules - Sunmin Jung; Park, Mikyoung (Academic Press, 2022)
Postsynaptic scaffolding proteins, which are major components of the postsynaptic density (PSD) at excitatory synapses, include Shank, PSD-95, A-kinase anchoring protein, Homer, and SAP90/PSD-95-associated protein families and play crucial roles in synaptic structure, signaling, and functions. Several genetic studies have indicated that postsynaptic scaffolding proteins contribute to the etiology of various psychiatric disorders, including neurodevelopmental disorders. Indeed, mice with mutations or deletions in specific genes encoding postsynaptic scaffolding proteins display alterations in behavioral phenotypes that are relevant to specific psy-chiatric disorders. Here, we review recent studies on various mutant mouse models of Shank postsynaptic scaffolding proteins associated with autism spectrum disorder, a major neurodevelopmental disorder, and discuss future directions and therapeutic strategies for the treatment of autism spectrum disorder.